Important Personal Values and Other Variables Determining Trust in the UN among European Peoples - Mücahit Aslan (Siyasal: Journal of Political Sciences)
The United Nations is becoming increasingly important as we approach a new phase in global governance because of the recent health, security, and economic crises that have emerged since the 2020s. In this conjecture, understanding the factors predicting trust in the UN is imperative. Designed to fill the gap in the relevant literature, this study employs the Eurobarometer 98.2 dataset to conduct a binary logistic regression analysis to measure the impact of personal values on trust in the UN among European peoples. Findings suggest that except for religion, all the values tested in this research are important predictors of trust in the UN. However, based on their higher exp(B) values and Wald statistics, values such as; human rights, equality, solidarity, and respect for the planet are more robust predictors of trust in the UN than values like the rule of law, respect for human life, peace, self-fulfillment, individual freedom, democracy, tolerance, and respect for other cultures. In addition to the personal values mentioned, this research also confirms the robustness of sociotropic and demographic variables such as economic insecurity, satisfaction with the political system, and education. Further research is needed to test the temporal and territorial significance of the findings.